2021
DOI: 10.1021/acs.molpharmaceut.1c00462
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniformity of Changes in Drug-Metabolizing Enzymes and Transporters in Liver Cirrhosis: Implications for Drug Dosage Adjustment

Abstract: Liver cirrhosis is a chronic disease that affects the liver structure, protein expression, and overall metabolic function. Abundance data for drug-metabolizing enzymes and transporters (DMET) across all stages of disease severity are scarce. Levels of these proteins are crucial for the accurate prediction of drug clearance in hepatically impaired patients using physiologically based pharmacokinetic (PBPK) models, which can be used to guide the selection of more precise dosing. This study aimed to experimentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 60 publications
(103 reference statements)
4
57
0
Order By: Relevance
“…Mostly similar results were reported by Billington et al [7] in chronic hepatitis C infection (but not stratified according to the liver functional state). An analysis of a small number of hepatitis C livers was also reported by El-Khateeb et al [9], who revealed downregulation of MRP2 and OATP2B1 proteins. A summary of the available proteomic information about drug transporters and carriers in hepatitis C is presented in Table 2.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Mostly similar results were reported by Billington et al [7] in chronic hepatitis C infection (but not stratified according to the liver functional state). An analysis of a small number of hepatitis C livers was also reported by El-Khateeb et al [9], who revealed downregulation of MRP2 and OATP2B1 proteins. A summary of the available proteomic information about drug transporters and carriers in hepatitis C is presented in Table 2.…”
Section: Discussionsupporting
confidence: 66%
“…Analysis of transporter abundance of all studies with hepatitis C patients suggests downregulation of NTCP, BSEP, and OCT1 uptake carriers and MRP2 efflux transporter, as well as stable levels of MRP3, BCRP, and OATP1B1. However, most of these studies did not provide detailed information about patient stratification according to the Child–Pugh classification, and only El-Khateeb et al [ 9 ] specified that the analysis included five patients from the Child–Pugh class A and four subjects from class B (without detailed protein abundance results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, CES1 is a vital drug metabolic enzyme in the liver that encodes about 1% of the total liver genomes ( 44 ). The liver inflammation or damage usually leads to alteration of liver drug-metabolizing enzymes, including CES1 ( 45 , 46 ). Consequently, the above results indicate that fluoride exposure affects the gene and protein expression levels of CES1 in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Although outside the scope of this review, physiological changes caused by hepatic impairment can alter drug pharmacokinetics and DDI magnitudes, with the liver being the main metabolizing organ for the vast majority of small drugs. Hepatic enzyme activity, blood flow, functional liver mass, plasma protein concentration, liver transporter mRNA level, and activity in hepatic impairment conditions have been evaluated; 20 , 21 , 22 , 23 however, their cumulative impact on varying DDI mechanisms remains unclear. For example, enzyme inhibition has been reported to decrease in people with hepatic impairment, whereas enzyme induction is suggested to remain unchanged.…”
Section: Hepatic Impairmentmentioning
confidence: 99%